Combining hypertension and chronic obstructive pulmonary disease: clinical features and approaches to treatment - Hnizdyukh, Roman Volodymyrovych; Smanko, Volodymyr Vasylovych (Journal of Education, Health and Sport, 2017)
In this article, we have presented the results of retrospective analysis of medical records of the patients suffering from chronic obstructive pulmonary disease in combination with arterial hypertension, who were treated at the in-patient department of Ternopil Municipal Hospital #3. We have clarified prevalence of this comorbidity and the pathogenic relation between arterial hypertension and COPD. The article provides data concerning intensity of clinical presentations, dynamics of arterial pressure as well as changes of instrumental and laboratory indexes of this patient group against the background of basic medication.